INVESTMENT AND CONSTRUCTION PROJECT AS AN OBJECT OF RISK ANALYSIS - I. Vlasenko; T. Shemyakina (Вестник университета)
This article describes the study and clarification of the essence of the category of «risk» as an economic component and object management in the sphere of investment and construction, the rationale for the initial assumptions of the risk as a key element of logic management decision in the implementation of ICP. As well as revealing the features and meaningful disclosure of the main problems of the analysis and assessment of risks in investment and construction activities.